Pronunciation repair : decreasing phonemic mispronunciations bt the Malay ESL speakers using pronunciation software - Ahmad Nasaruddin, Sulaiman; Kassim, Asiah; Nor Ashikin, Abdul Aziz; Yap, Chui Yan (2006)
The study focuses on one of pronunciation elements, which is the production of phonemic correctness. The subjects involved are Malay ESL speakers and the aims are to identify the most common consonant mispronunciations committed by these speakers and to use pronunciation software, which is the Pronunciation Power developed by English Computerized Learning Inc. (ECL), to correct the errors. The purpose of using the software is to see the effectiveness in assisting learners in the learning process. Based on the research done on 300 initial participants, it is found that the common mispronounced consonants among Malay ESL speakers are /3/, /θ/ and /ð/, which do not exist in the first language phonological system. Once the mispronunciations are identified 20 participants were selected to go through a 30-hour treatment using the software. By the end of the session, most of them managed to self-correct the errors in their controlled speech. However, in natural speech setting, the mispronunciations persist. By carrying out this study, it is the expectation of the researchers that some insights can be provided for further research. Furthermore, findings gathered are also hoped to contribute to the development of academic syllabus to be implemented as an elective course that educators in the university can offer to the students as an enhancement in learning second language.